From the Backroom to the Front Line: Making Constitutional History or Encounters with the Constitution: Patriation, Meech Lake, and Charlottetown - Dawson, Mary (McGill Law Journal / Revue de droit de McGill, 2012)
Toward the end of the previous century, Canadians experienced an unprecedented period of constitutional activity involving changes and proposed changes to our constitution, three referendums, and a series of important court decisions. The patriation of the constitution of Canada was formally proclaimed in Canada on April 17, 1982. The new amending formula was tested in a series of constitutional negotiations. The two most prominent of the proposed amendments, the Meech Lake and Charlottetown Accords, although ultimately unsuccessful, had a very significant impact. A number of other, less extensive amendments were achieved with little controversy. In this lecture, as drafter of the proposed amendments and former legal advisor to the Government of Canada, I will look back on the drama of these events, paying particular attention to the context in which they took place, the different processes that were carried out, the events that were taking place in the backrooms, and the aftermath of some of these initiatives.